Phenocam - Green and Red Chromatic Coordinates time series from Skogaryd Stordalen Catchment, Mast 5.9m Phenocam 01, 2013–2021 - Skogaryd Research Catchment (University of Gothenburg, 2022)
Spectral indices from different ecosystems within the SITES Spectral network, collected by phenocameras on towers. Records are averaged daily from phenocam composites of photos from 10 a.m. to 2 p.m. within specific regions of interest (ROI).
Skogaryd Research Catchment (2022). Phenocam - Green and Red Chromatic Coordinates time series from Skogaryd Stordalen Catchment, Mast 5.9m Phenocam 01, 2013–2021 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/YMXKziV3Q-irdntIYLw500Em
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Time instant; Time instant; Daily averaged value of Red Channel; Daily averaged value of Red Channel; Daily averaged value of Green Channel; Daily averaged value of Green Channel; Daily averaged value of Blue Channel; Daily averaged value of Blue Channel; Daily averaged Green Chromatic Coordinate; Daily averaged Green Chromatic Coordinate; Standard deviation of the corresponding daily averaged GCC; Standard deviation of the corresponding daily averaged GCC; Daily averaged Red Chromatic Coordinate; Daily averaged Red Chromatic Coordinate; Standard deviation of the corresponding daily averaged RCC; Standard deviation of the corresponding daily averaged RCC; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap